Effective load management technique for AI characters in games - Tan, Brian. (2009)
Creating large populations of AI characters for game environment is a major challenge because either insufficient CPU processing time is available or it is difficult to balance the computational needs of the game AI against the requirements of other game components. We present a novel technique that allows games to manage the functional updates of AI characters efficiently during run time. The technique is an enhancement of the elastic task model and scheduling [BLCA02] which allows the total CPU utilization of the AI characters to bead justed to the current workload of the game. We exploited the elastic nature of the technique to provide Level of Detail(LOD)effect for the AI characters. A prototype implementation on Microsoft Xbox 360 hardware is described in this paper.